(untitled) (American Journal of Agricultural Science, Engineering, and Technology, 2025)
This study aimed to assess the impact of production location on the postharvest physiochemical attributes of BARI Mango-4. For this reason, mature ripe fruits of BARI Mango-4 were obtained from two different locations: Rajshahi and Sylhet district of Bangladesh. Fruits from both locations were then preserved for 5 days at room temperature, when they reached an ideal stage for processing. Various physical and chemical characteristics of the fruits such as- fruit weight, size of the fruit and seed in terms of length, width and thickness, proportions of peel, seed, edible portion, dry matter and total soluble solids, pH, vitamin C, anthocyanin, beta-carotene and antioxidant activity were estimated in 4 replications. The individual fruit weight of BAR Mango-4 obtained from the Rajshahi district was remarkably higher when compared to the Sylhet district. Significantly higher length and width of the Rajshahi district-grown mango contributed to the higher individual fruit weight. In addition to these, total soluble solids, vitamin-C, beta-carotene and antioxidant activity of the mangoes assembled from the Rajshahi district were markedly higher. Compared to the Rajshahi district, the Sylhet district-grown BARI Mango-4 had a higher value for the fruit hardness, dry matter content and edible portion. The results indicate a significant impact of the production location on the postharvest physiochemical attributes of BARI Mango-4. Studies identifying the factors that have impact on the mango fruit quality will help to enhance the postharvest quality of the fruits to meet the market requirements.